Practical Economics Economic Transformation and Government Reform in Georgia 2004–2012 - Gilauri, Nika (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is open access under a CC BY license. In this book, Nika Gilauri reveals his formulas for government reform and economic recovery, including how to fight against corruption, reform fiscal policy and tax systems, privatize state-owned enterprises, build a welfare system for those most in need, create a competitive education and healthcare system, and streamline procurement. All formulas are corroborated by practical experience and empirical evidence gathered during Mr Gilauri's term as a cabinet member (2004-2009) and prime minister (2009-2012) of Georgia, and provide an in-depth view of what worked in the case of Georgia since 2003, and how lessons learned could be applied in other parts of the world.